2010
DOI: 10.1177/1012690210384661
|View full text |Cite
|
Sign up to set email alerts
|

Transgender inclusion and the changing face of lesbian softball leagues

Abstract: This article examines the re-negotiation of sex-based boundaries within the context of transgender/transsexual inclusion in North American lesbian softball leagues. Semi-structured interviews with transgender participants combined with participant observation have been undertaken. We focus on the ‘climate’ ( Hall and Sandler, 1982 ) for transgender participation in lesbian softball leagues that have adopted radical (non sex-binary-based) transinclusive policies. The majority of our research participants report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 25 publications
0
55
0
1
Order By: Relevance
“…The majority of the studies were qualitative in nature, all of which employed interviews [24–29]. The remaining two research articles included an experimental study [23] and a cross-sectional survey [30].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies were qualitative in nature, all of which employed interviews [24–29]. The remaining two research articles included an experimental study [23] and a cross-sectional survey [30].…”
Section: Resultsmentioning
confidence: 99%
“…Positive effects from sports on mental well-being and social involvement in welcoming, safe, and comfortable sports settings strengthen transgender individuals' abilities to cope with challenges (Elling-Machartzki, 2015;Elling and Collot d'Escury, 2017). Several studies have identified safe spaces in sport, in which transgender athletes were accepted, socially supported by the team, and enabled to compete without rigid restrictions (Lucas-Carr and Krane, 2012, Travers andDeri, 2010;Elling and Collot d'Escury, 2017). But as these conditions are rather rare in mainstream sports settings, establishing trans-only sporting environments might externally facilitate transgender sports participation (Jones et al, 2017a).…”
Section: Transgender Athletes' Experiencesmentioning
confidence: 99%
“…As we outline in subsequent sections, structural stigma also manifests through sport-governing bodies' regulations and policies (Buzuvis, 2012;Carroll, 2014;Krane, Barak, & Mann, 2012;Love, 2014;Travers & Deri, 2011). In many states, for example, high school athletes must participate in sports or on teams that match their sex assigned at birth.…”
Section: Structural Stigmamentioning
confidence: 99%